Are free school meals failing families? Exploring the relationship between child food insecurity, child mental health and free school meal status during COVID-19: national cross-sectional surveys. Issue 6 (9th June 2022) - Yang, Tiffany C; Power, Madeleine; Moss, Rachael H; Lockyer, Bridget; Burton, Wendy; Doherty, Bob; Bryant, Maria
Abstract : Objective: Food insecurity is linked to poor health and well-being in children and rising prevalence rates have been exacerbated by COVID-19. Free school meals (FSM) are considered a critical tool for reducing the adverse effects of poverty but apply a highly restrictive eligibility criteria. This study examined levels of food security and FSM status to support decision-making regarding increasing the current eligibility criteria. Design: Two cross-sectional national surveys administered in August–September 2020 and January–February 2021 were used to examine the impact of COVID-19 on the food experiences of children and young people. Setting: UK. Participants: 2166 children (aged 7–17 years) and parents/guardians. Main outcome measures: Participant characteristics were described by food security and FSM status; estimated marginal means were calculated to obtain the probability of poor mental health, expressed as children reporting feeling stressed or worried in the past month, by food security status and FSM status. Results: We observed food insecurity among both children who did and did not receive of FSM: 23% of children not receiving FSM were food insecure. Children who were food insecure had a higher probability of poor mental health (31%, 95% CI: 23%, 40%) than children who were food secure (10%, 95% CI: 7%, 14%). Food insecure children receiving FSM had a higher probability of poor mental health (51%, 95% CI: 37%, 65%) than those who were food insecure and not receiving FSM (29%, 95% CI: 19%, 42%). Conclusion: Many children experienced food insecurity regardless of whether they received FSM, suggesting the eligibility criteria needs to be widened to prevent overlooking those in need.